2000
DOI: 10.4049/jimmunol.165.10.5443
|View full text |Cite
|
Sign up to set email alerts
|

Thymocytes Express thegolliProducts of the Myelin Basic Protein Gene and Levels of Expression Are Stage Dependent

Abstract: The golli products of the myelin basic protein gene have been shown to be expressed in mouse thymus and brain. The full repertoire of thymic cell types expressing golli products has not yet been determined, although immunoreactivity has been found in some macrophages. We have analyzed the cellular expression of golli mRNAs and proteins in the thymus. The results showed that MTS5+ cortical/MTS10+ medullary epithelial cells and NLDC145+ dendritic cells did not express golli, while some macrophages did exhibit st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…The report by J.-M. Feng et al (31) of HMBP RNAs in thymus cells showed that these quite unexpected data were reproducible and that indeed T cells do produce HMBP proteins. However, we did not observe ''altered levels of expression in developing thymocytes and lack of significant expression in thymic stromal cells,'' and furthermore, HMBP was not detected within T cell nuclei, as J.-M. Feng et al reported, even at the ultrastructural level.…”
Section: Discussionmentioning
confidence: 90%
“…The report by J.-M. Feng et al (31) of HMBP RNAs in thymus cells showed that these quite unexpected data were reproducible and that indeed T cells do produce HMBP proteins. However, we did not observe ''altered levels of expression in developing thymocytes and lack of significant expression in thymic stromal cells,'' and furthermore, HMBP was not detected within T cell nuclei, as J.-M. Feng et al reported, even at the ultrastructural level.…”
Section: Discussionmentioning
confidence: 90%
“…A series of immunological studies performed by Voskuhl's group showed that the MBP epitopes within golli proteins could be recognized by T-cells lines derived from SJL mice specific for the immunodominant (MBP 83-102 ) and subdominant (MBP [19][20][21][22][23][24][25][26][27] ) epitopes, implying that the golli protein could potentially serve as an additional source of MBP epitopes [7,8]. During relapsing experimental autoimmune encephalomyelitis (EAE), the response of T-cells spreads to epitopes other than the disease-initiating myelin protein epitopes.…”
Section: Golli Proteins As Myelin-related Self-antigensmentioning
confidence: 99%
“…In mouse, three golli products have been identified: BG21, J37, and TP8 . Unlike the classic MBPs, golli proteins are expressed in myelin-forming cells as well as in neurons in the CNS and peripheral nervous system (Landry et al, , 1997(Landry et al, , 1998Pribyl et al, 1996) and in macrophages and T-cells in the immune system (Feng et al, 2000). Golli proteins first appear in many neurons when they are extending processes for migration, establishment of connections and, in the case of oligodendrocytes (OLs), before myelination (Landry et al, , 1997(Landry et al, , 1998Pribyl et al, 1996).…”
Section: Introductionmentioning
confidence: 99%